Chatbot-mediated technology to enhance experiences in historical textile museums - Supaporn Chai-Arayalert; Supattra Puttinaovarat; Wanida Saetang (Cogent Arts & Humanities)
This study aimed to enhance visitor engagement and interactions with historical textile exhibits in small museums by implementing a Hand-i-Craft Bot. Our research aligns with the broader trend of leveraging technology to improve museum experiences. This research addressed the challenge of increasing engagement and understanding of historical textiles in small museums. We employed an experimental research methodology grounded in a design thinking approach, which involved developing the Hand-i-Craft Bot and evaluating its usability. This research utilized the Namuensri Textile Museum as a case study. The assessment used the System Usability Scale (SUS), Net Promoter Score (NPS), and user satisfaction, robustly measuring the chatbot’s effectiveness. The results showed that the chatbot had a SUS score of 74.92. The most common response was ‘excellent’, indicating good usability. The average grade of a B was another positive usability experience indicator. The NPS score of ‘promoter’ showed that most participants would likely recommend the chatbot to others. User satisfaction results indicate that the Hand-I-Craft Bot is an effective tool for enhancing visitors’ museum experiences. By providing information, being consistent and informative, and making the visit more interesting, the Hand-I-Craft Bot increased user engagement and enhanced visitors’ experiences.